Eco-agriculture and Renewable Energy System Concept for a Rural Community in Ghana. Issue 1 (September 2020) - Mao, Junqi; Addanki, T; Gebhard, M; Ghio, F; Li, Haomin
Abstract: Eco-agriculture is the trend of rural development in this age. This research uses the moringa tree as an example to build up the eco-agricultural and renewable framework for a typical village in Ghana. An energy balance is analyzed using an urbs tool, while business and financial models are built up following MVP (minimum viable product).